Self Assessment Questions in General Surgery. Issue 3 (1st September 2009) - Morgan, J; Garner, Jeff
Abstract : The advent of Modernising Medical Careers has meant that many more junior doctors are coming into contact with general surgical patients either as part of Foundation Year 2 or Core Training rotation or during the course of cross covering other specialities due to the hours constraints of the European Working Time Directive. These scenarios are all common general surgical cases that such a junior doctor may be expected to manage.